Complete Replacement of Fishmeal With Plant Protein Ingredients in Gibel Carp (Carassius auratus gibelio) Diets by Supplementation With Essential Amino Acids Without Negative Impact on Growth Performance and Muscle Growth-Related Biomarkers - Cai, Wanjie; Liu, Haokun; Han, Dong; Zhu, Xiaoming; Jin, Junyan; Yang, Yunxia; Xie, Shouqi (Frontiers in Marine Science, 2022)
This study was conducted to investigate the effects of substitution of dietary fishmeal (FM) by compound plant protein supplemented with essential amino acids on growth performance, plasma physiology, and muscle growth-related genes of gibel carp (Carassius auratus gibelio). Four diets with equal digestible protein were prepared, where 30FM (control feed) contained 30% FM and land animal protein as a protein source, 10FM contained 10% FM, PMAa contained full plant meal (PM) supplemented with crystalline amino acid, and PM contained full PM feed. There was no significant difference in the specific growth rate (SGR) with 30FM, 10FM, and PMAa diets (p > 0.05); however, the SGR of PM group was the lowest with significant difference (p < 0.05). Feed efficiency of the PM group was the lowest with significant difference (p < 0.05). The whole-body crude protein content of fish in PMAa group was significantly higher than that in each group with additional FM (p < 0.05). There were no significant differences in plasma total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C) or low-density lipoprotein cholesterol (LDL-C), and free amino acid profile of 30FM, 10FM, and PMAa groups (p > 0.05); however, they were significantly higher than that in PM group (p < 0.05). The expression of key genes in the TOR signaling pathway (tor, s6k1, 4e-bp2, and eif4e), autophagy (ulk1 and atg13), and ubiquitin–proteasome (trim63 and znrf2) system of the PMAa group was similar to that of the FM group (p > 0.05), indicating that the muscle growth-related biomarker genes were positively regulated by the appropriate dietary amino acid composition at the transcriptional level. These results suggest that FM in gibel carp diet can be totally replaced by PM without negative impact on growth performance and muscle growth-related biomarkers at the transcriptional level, which provided the requirement of digestible protein and balanced amino acid profile is satisfied.